Participation of people with psychosocial disability in mental health policy development in South Africa - Kleintjes, Sharon Rose (Department of Psychiatry and Mental Health, 2014)
This study addressed the following question: What are the barriers and strategies to support the participation of South Africans with psychosocial disability in mental health policy development in South Africa? A systematic literature review (objective 1) addressed the question: ""What supports people with psychosocial disability to participate in national mental health policy development?"" The WHO Checklist for Mental Health Legislation, the WHO Checklist for Mental Health Policy and Plan, and domain 4 of the World Health Organisation Assessment Instrument for Mental Health Systems (WHO-AIMS) were completed, and 96 semi-structured interviews with key stakeholders were conducted, to assess current stakeholder, mental health legislation and policy support for the participation of people with psychosocial disability in South Africa (Objective 2). Nvivo-7 software was used to analysis qualitative data, using a framework analysis approach to data analysis and interpretation. These interviews were also used to ascertain the views of 56 of the 96 South African stakeholders' involved in mental health services, on environmental barriers to the participation of people with psychosocial disability in mental health policy development in South Africa (objective 3). The remaining 40 interviews with people with psychosocial disability documented their lived experience of barriers to their participation in policy development, and highlighted their priorities for policy development (Objective 4). Eleven key informants involved in leadership roles in peer led organisations for people with psychosocial disability in Africa were interviewed to inform understanding of opportunities for supporting people with psychosocial disability to participate in mental health policy development (Objective 5). The findings of objectives 1-5 were triangulated to inform the development of a conceptual framework for supporting South Africans with psychosocial disability to participate in mental health policy development (objective 6). The framework proposes the need for social transformation to overcome barriers to the inclusion of people with psychosocial disability in society, including as policy participants, support for self-directed agency, and opportunity for meaningful participation in policy development.